A dinâmica do espaço devocional sertanejo: a devoção a Padre Cícero e sua contribuição na constituição da identidade do sertanejo - Amaral, Wagner Lima (2014)
The dynamics of backcountry devotional space - Devotion to Padre Cicero and his contribution to the establishment of the identity of the backwoods frontiersman has devotion to Padre Cicero, being held through extensive literature review by historiographical, analytical and poetic works as an object of study. Part of the analysis of the place of the backcountry - the hinterlands, and finds it difficult to experience instead the motivation for the invention of a particular space, through their devotion, establishing life expectancy. This space creates a dynamic of transcendence x immanence in he transcends his place through his connection with the reference to his devotion - Padre Cicero, adding to its binding interaction with their peers - the devout pilgrims; and thus realize the immanence of the divine in his place for the practice of their faith, by its dimensions: collective, by orality; performative, for pilgrimages; and literary, by twine. The preservation of this space through devotion, not only establishes new dynamics for the backcountry suffered as influences decisively on its own identity by adding or emphasizing features like a poetic vision of reality, an appropriation of symbols, a resistance to hopelessness, an understanding mystical life. These characteristics influence the formation of their identity, making the author and actor in your own reality, inventor of a beautiful dynamic and hope for life; in which reframes ancient knowledge, making them applicable in its new contexto, creating a resilient hope in which all reality is understood, interpreted and lived in a strong Christian mystical tone, bringing meaning to this life and to come, a triumphal eschatological perspective. So, is the devotee who determines the preservation of life through the backcountry of your space